Peran Guru Aqidah Akhlak dalam Membentuk Akhlakul Karimah Siswa Kelas VIII di SMPIT Al-Irsyad Al-Islamiyyah Karawang - Novia Asri Rahayu; Tajudin Noor; Abdul Kosim (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
This study aimed to determine the role of the moral aqidah instructor at the SMPIT AL-Irsyad Al-Islamiyyah Karawang school through direct field research. This research employs a qualitative method approach and field research in which the researcher immediately enters the field to learn more about the function of the moral aqeedah instructor at SMPIT Al-Irsyad Al-Islamiyah Karawang. Observation, interviews, and documentation are the methods used for data gathering in this study. Data analysis including the selection of collected data, its integration, processing, and analysis to form conclusions. According to the findings, the function of instructors, particularly professors of moral aqidah, at SMPIT AL-Irsyad Al-Islamiyyah Karawang is quite significant. In teaching his students morality. As an exemplary and required educator, the teacher must also possess high moral standards. In this way, the teacher not only imparts knowledge, but also sets a positive example for his students every day at school. Consequently, the job of the teacher in learning is that of a mentor, assistant, motivator, innovator, and evaluator.